2020
DOI: 10.3390/s21010141
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Evaluation of Selected Mobile Inspection Robot Localization Techniques in a GNSS-Denied Environment

Abstract: Locating an inspection robot is an essential task for inspection missions and spatial data acquisition. Giving a spatial reference to measurements, especially those concerning environmental parameters, e.g., gas concentrations may make them more valuable by enabling more insightful analyses. Thus, an accurate estimation of sensor position and orientation is a significant topic in mobile measurement systems used in robotics, remote sensing, or autonomous vehicles. Those systems often work in urban or undergroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…More research focusing on the techniques and applications related to the mobile robot-based platform for structural damage inspection and various purposes has been widely conducted as presented in Table 3, such as non-structural damage inspection, 94 pipeline inspection, 95,96 localization techniques of inspection-aimed mobile robots. 97 These previous studies demonstrated that increasing attention is paid to mobile robot technology which can be applied in practice for damage inspection in various scenarios, and is able to perform more tasks, such as repair of pipelines. However, only a few studies of using mobile robot technology in damage inspection of building structures have been found, which indicates the potential to explore the feasibility of mobile robots for collecting data and inspecting the damage to buildings, as well as to evaluate their performance and application prospect in the practice.…”
Section: Mobile Robot Application In Damage Inspectionmentioning
confidence: 99%
“…More research focusing on the techniques and applications related to the mobile robot-based platform for structural damage inspection and various purposes has been widely conducted as presented in Table 3, such as non-structural damage inspection, 94 pipeline inspection, 95,96 localization techniques of inspection-aimed mobile robots. 97 These previous studies demonstrated that increasing attention is paid to mobile robot technology which can be applied in practice for damage inspection in various scenarios, and is able to perform more tasks, such as repair of pipelines. However, only a few studies of using mobile robot technology in damage inspection of building structures have been found, which indicates the potential to explore the feasibility of mobile robots for collecting data and inspecting the damage to buildings, as well as to evaluate their performance and application prospect in the practice.…”
Section: Mobile Robot Application In Damage Inspectionmentioning
confidence: 99%
“…Whereas the additional radial component can be written as shown in Equation (6). In Equation (6), the radial acceleration component is equivalent to the product of the radius ( ) at which the accelerometer is mounted on the wheel and the squared angular rate ( ) of the spinning wheel.…”
Section: = Cos( ± ) + (5)mentioning
confidence: 99%
“…The radial acceleration component is caused due to an eccentricity ( ) in mounting the AWOK IMU to the wheel, where the centroid of the IMU does not coincide with the wheel center. Hence, by using the formula shown in Equation (6), that radial acceleration component increases quadratically with the angular rate of the wheel ( ). Consequently, the superimposed radial acceleration trend can be computed using Equation (6).…”
Section: Accelerometer Input Rangementioning
confidence: 99%
See 2 more Smart Citations